2019
DOI: 10.3389/fimmu.2019.01463
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Gene Expression Profiles of Monocytes and Lymphocytes From Peste-Des-Petits-Ruminants Virus Infected Goats

Abstract: In this study, transcriptome analysis of PPRV infected PBMC subsets—T helper cells, T cytotoxic cells, monocytes, and B lymphocytes was done to delineate their role in host response. PPRV was found to infect lymphocytes and not monocytes. The established receptor for PPRV—SLAM was found downregulated in lymphocytes and non-differentially expressed in monocytes. A profound deviation in the global gene expression profile with a large number of unique upregulated genes (851) and downregulated genes (605) was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…In experiments with the Sungri/96 PPRV vaccine virus, IFN-α/β mRNA were not detected after the infection of PBMC [31] and evasion of IFN-induced antiviral effects by PPRV have been shown to occur through miRNA mediated regulation of IRF3 and IRF7 [32]. In contrast, studies with a virulent PPRV strain demonstrated that genes within the interferon and RIG-1 like receptor signaling pathway, IRF-7 and STAT-1 that regulate the expression of ISGs, were active in lymphocytes [33]. Our previous report also indicates the contribution of TLR7 mediated higher IFN alpha induction as a factor for the lower replication of PPRV in cattle PBMC [17].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In experiments with the Sungri/96 PPRV vaccine virus, IFN-α/β mRNA were not detected after the infection of PBMC [31] and evasion of IFN-induced antiviral effects by PPRV have been shown to occur through miRNA mediated regulation of IRF3 and IRF7 [32]. In contrast, studies with a virulent PPRV strain demonstrated that genes within the interferon and RIG-1 like receptor signaling pathway, IRF-7 and STAT-1 that regulate the expression of ISGs, were active in lymphocytes [33]. Our previous report also indicates the contribution of TLR7 mediated higher IFN alpha induction as a factor for the lower replication of PPRV in cattle PBMC [17].…”
Section: Discussionmentioning
confidence: 97%
“…Viral infection-induced interferons induce an exclusive and moderately overlapping set of interferon stimulated genes (ISG) and studies have identified 50 to 1000 ISGs (using microarrays) that are typical to some cells types with effector functions limited to the classical ISGs, namely protein kinase (PKR; also known as eukaryotic translational initiation factor 2-alphase kinase -EIF2AK2), Myxovirus Resistance Protein 1 (MX1), 2 -5 -oligoadenylate synthetase 1 (OAS1), Tripartite Motif Containing 5 (TRIM5), Interferon-stimulated gene 15 (ISG15), adenosine deaminase acting on RNA (ADAR), interferon-induced transmembrane protein 1/2/3 (IFITM1/2/3 also called CD225), Tetherin (also known as BST2 or CD17), Viperin (also known as Radical S-Adenosyl Methionine Domain Containing 2 -RSAD2) [34,35] and ATP-dependent dsRNA helicase DHX58 also known as RIG-I-like receptor LGP2 (RLR) [36]. Up-regulation of the ISGs (ISG15, Mx1, Mx2, RSAD2, IFIT3 and IFIT5) that play a role in antiviral response and the viral sensors MDA5, LGP2 and RIG1 were found to up-regulated in lymphocytes upon exposure to a virulent strain of PPRV [33]. Our RNAseq data also reveal that the IFN type I responses are highly up-regulated in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome profiling by RNA-seq is the most common methodology to study the changes in systems biology. RNA profiling based on next-generation sequencing enables to measure and compare gene expression patterns [16]. The global transcriptome of Tharparkar and Crossbred indicated differential response to heat stress as evident from the DEGs, that are either distinct to both or have a difference in expression.…”
Section: Discussionmentioning
confidence: 99%
“…The systems biology behind a phenotype is most commonly studied by transcriptome profiling [14,15]. RNA-seq is a high throughput approach to measure relative global changes in the transcripts under specific condition(s) [14,16,17]. RNA -seq allows for analysis of transcriptome in an unbiased way, with, a tremendous dynamic detection range (>8,000 fold), and low background signals [18].…”
Section: Introductionmentioning
confidence: 99%
“…The counts were used for calculating differentially expressed genes (DEGs) by use of R packages -EBSeq, DESeq2, edgeR. The common DEGs from the three packages were used for downstream analysis while fold changes for the corresponding genes were taken from DESeq2 [24].…”
Section: Raw Data Processingmentioning
confidence: 99%